Clinical Presentation, Natural History, and Therapeutic Approach in Patients with Solitary Fibrous Tumor: A Retrospective Analysis. (27th March 2020) - Schöffski, P.; Timmermans, I.; Hompes, D.; Stas, M.; Sinnaeve, F.; De Leyn, P.; Coosemans, W.; Van Raemdonck, D.; Hauben, E.; Sciot, R.; Clement, P.; Bechter, O.; et al.
Abstract : Background . Solitary fibrous tumor (SFT) is a rare variant of soft tissue sarcoma (STS). Materials and Methods . We reviewed SFT patients (pts) treated at our institution between 12/1990 and 09/2017. Results . We identified 94 pts with a median follow-up (mFU) of 4.7 years (range: 0.1–21.53). Primary sites were the chest (33%), abdomen (21.3%), brain (12.8%), and extremities (9.6%); 6.4% of pts presented with synchronous metastasis. Median overall survival (mOS) from the first diagnosis was 56.0 months (m) (0.3–258.3). Doege–Potter syndrome was seen in 2.1% of pts. Primary resection was performed in 86 pts (91.5%). Median progression-free survival was 34.1 m (1.0–157.1), and 43% of pts stayed SFT-free during FU. Local recurrence occurred in 26.7% after a mFU of 35.5 m (1.0–153.8), associated with an OS of 45.1 m (4.7–118.2). Metachronous metastasis occurred in 30.2% after a mFU of 36.0 m (0.1–157.1). OS in metastatic pts was 19.0 m (0.3–149.0). Systemic therapy was given to 26 pts (27.7%) with inoperable/metastatic disease. The most common (57.7%) upfront therapy was doxorubicin, achieving responses in 13.3% of pts with a PFS of 4.8 m (0.4–23.8). In second line, pts were treated with ifosfamide or pazopanib, the latter achieving the highest response rates. Third-line treatment was heterogeneous. Conclusion . SFT is an orphan malignancy with a highly variable clinical course and a considerable risk of local failure and metachronous metastasis. Surgery is the only curative option; palliative systemic therapy is used in inoperable/metastatic cases but achieves low response rates. The highest response rates are seen with pazopanib in second/third line.